Pericytes improve locomotor recovery after spinal cord injury in male and female neonatal rats. (28th August 2020) - Mayo, Jamie N.; Kauer, Sierra D.; Brumley, Michele R.; Bearden, Shawn E.
Abstract: Objective: It is not known how activation of the hypoxia‐inducible factor (HIF) pathway in pericytes, cells of the microvascular wall, influences new capillary growth. We tested the hypothesis that HIF‐activated pericytes promote angiogenesis in a neonatal model of spinal cord injury (SCI). Methods: Human placental pericytes stimulated with cobalt chloride and naïve pericytes were injected into the site of a thoracic hemi‐section of the spinal cord in rat pups on postnatal day three (P3). Hindlimb motor recovery and Doppler blood flow perfusion at the site of transection were measured on P10. Immunohistochemistry was used to visualize vessel and neurofilament density for quantification. Results: Injection of HIF‐activated pericytes resulted in greater vascular density in males but did not result in improved motor function for males or females. Injection of non–HIF‐activated pericytes resulted improved motor function recovery in both sexes (males, 2.722 ± 0.31‐fold score improvement; females, 3.824 ± 0.58‐fold score improvement, P  < .05) but produced no significant changes in vessel density. Conclusions: HIF‐activated pericytes promote vascular density in males post‐SCI. Acute delivery of non–HIF‐activated pericytes at the site of injury can improve motor recovery post‐SCI.